Exceptional Agulhas leakage prolonged interglacial warmth during MIS 11c in Europe. (12th November 2014) - Koutsodendris, Andreas; Pross, Jörg; Zahn, Rainer
Abstract The transport of warm and saline surface water from the Indo‐Pacific Ocean into the South Atlantic ("Agulhas leakage") influences the Atlantic Meridional Overturning Circulation (AMOC), which in turn exerts control on European climate. Paleoceanographic data document a remarkably strong Agulhas leakage at the end of marine isotope stage (MIS) 11c interglacial (~400 ka B.P.), which is one of the best orbital analogues for the Holocene. Here we assess the potential influence of this exceptional Agulhas leakage on North Atlantic climate based on a compilation of marine and terrestrial proxy records from the Iberian margin and continental Europe. We show that a ~5 ka long warm period persisted across Europe beyond the MIS 11c climatic optimum. This warm period is testified by increases in foraminifer‐derived sea surface temperatures on the Iberian margin, a spread of temperate trees on Iberia, and the expansion both of evergreen trees and thermophilous diatom taxa in Central European lowlands. Paradoxically, this warming coincides with an insolation minimum, implying that orbital forcing can be excluded as the underlying cause. We conclude that persistent warmth during weak insolation at the end of MIS 11c in Europe may have been triggered by strengthened Agulhas leakage, which stimulated a vigorous AMOC and increased the northward transport of warm surface waters to higher latitudes via the North Atlantic Current. The close analogy of the present and MIS 11c orbital forcing underlines the possibility that the present‐day increase of the Agulhas leakage, although driven by different forcing than MIS 11c, may considerably affect future climates across Europe.